The Defeathering Effect by Scalding in Chickens Follows Their Intrinsic Dermal Histologies - Shung, Chia-Cheng; Hsin, Kun-Yi; Tan, Fa-Jui; Chen, Shuen-Ei (Animals (Basel), 2023)
This study aimed to delineate the fundamental skin histology and its association with feathers in broilers and native Red-Feather (RF) chickens and further elucidate their thermal alterations in respect to the defeathering effect by scalding. Comparisons of skin thickness between fresh samples and those after dehydration and fixation, as well as their collagen contents and histological differences, suggested that RF chickens had a thicker dermal layer with more collagen deposition and compact architecture, particularly in the neck and abdominal skin, but a thinner hypodermal layer in the back, chest, and abdomen skin. Despite an adolescent age, RF chickens showed a shorter calamus depth of tail feathers but a larger calamus diameter of wing feathers. Within the feather follicle punch, a very intense follicle sheath layer with compact collagenous matrixes to fulfill the space next to the inner feather root sheath was observed in RF chickens. Under both soft and hard scalding, RF chickens showed a lower degree of denaturation on hip skins and were more resistant to structural disintegration, primarily within the epidermal and dermal layer. Accordingly, a much narrower gap space between the feather sheath and surrounding follicle sheath was observed, and the gap expansion was also resistant to thermal changes. These results suggest that the defeathering effect by scalding follows the intrinsic skin histologies in chickens of various breeds and ages, primarily depending on the interaction of the feather calamus with the surrounding follicle sheath and neighboring cutaneous tissues, reflecting their resistance to thermal denaturation, but is irrelevant to the feathers per se.